Increased Productivity through a Production Model Based on Lean Manufacturing and SLP Tools in Small Furniture Manufacturing Workshops - Kawakami Arevalo, Sayuri (2023)
The furniture industry has developed globally with exponential growth in recent years. In Peru, it is one of the key sectors in the productive transformation chain that is growing the most. However, these companies are mostly microenterprises and present various challenges such as the lack of quality standards, the high need for labor, the lack of qualified workers, limitations in technology, among others, which leads to low productivity and performance. That said, the main objective of this research is to increase the productivity of a Peruvian SME workshop dedicated to the man- ufacture of melamine furniture on a small scale. For this purpose, a model composed of the tools Systematic Layout Planning (SLP), 5’S and Standard Work (SW) was proposed and executed through a pilot plan and simulation. As a result, there was an increase in productivity by 11.82%, an increase in production by 50% and a reduction in production time from 398 min to 330.67 min.